EFEK LESSON STUDY TERHADAP PENINGKATAN KOMPETENSI PEDAGOGIK CALON GURU - Rizki, Swaditya (UNIVERSITAS MUHAMMADIYAH METRO, 2014)
The aims of this research was to know difference increasing especiallyÂ ability in Plan and Do between lesson study-based learning and not(conventional) learning. Furthermore, the second aim was to know the effect of lesson study toward increasing of pedagogy competency and impact of prospective teachers in teaching. The methodology of this research was using descriptive qualitative with amount of prospective teachers is 13, then the prospective teachers conducted Plan and Do respectively 3 times meeting using lesson study and conventional. The results showed that the effect was very positive where the learning process of Plan and Do using lesson study was better than conventional learning. Besides that, based on the observation and valuation showed that lesson study-based learning was better than conventional learning. The effect could also influence for students and prospective teacher positively.Â Kata Kunci: Lesson Study, Kompetensi Pedagogik, Calon Guru.